Sequencing, Evolutionary Relationship and 3D-StructureAnalysis of Interferon-ε Gene of Rabbit(Oryctolagus cuniculus) - Kanagarajadurai, Karuppiah; Nagarajan, Govindasamy; Thirumaran, Sumangali Mottai Kuppusamy; Pachaiyappan, Kuppachari; Pandian, Sankariah Jegaveera; Thirumurugan, Palanisamy; Murali, Govindarajan; Rajendiran, Aeripudur Sellappan (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was carried out with the objective to clone and characterize the full-length gene of IFNε of rabbit.  The cDNA of type  I interferon, viz., Interferon-ε from the liver of a rabbit was amplified by conventional RT-PCR and subsequently cloned for sequence  analysis. The obtained nucleotide sequence and the corresponding amino acid sequences of IFN-ε gene were analyzed by using  standard bioinformatic tools. A 3D model structure of rabbit IFNe was constructed using a multi-template model employing MODELLER  algorithm. Like other IFNε, the rabbit IFNε cDNA also contained a 573-bp open reading frame encoding a protein of 190 amino acids  with an estimated molecular weight of 20.90 kDa. Sequence analysis revealed that rabbit from India shared 100 % both at nucleotide  and amino acid levels with that of two other sequences available in the NCBI database. Three Cys residues at positions 53, 163 and 175  were found to be conserved across the primary structure of orthologs. Phylogenetic analysis based on amino acid sequences indicated  the close relationship in Interferon-ε gene between rabbit and other lagomorphs. The model structure of rabbit IFNε also had the similar  pattern to that of any determined type-1 interferon structures, which contained five alpha helices. The 3D-structure was predicted to be  stabilized by a disulphide bond, which was found between the residues 53 and 163 and is conserved across the ortholog IFNε protein  sequences. It was observed that the genetic diversity between human and rabbit is lower when compared to that between human and  mouse. The study also predicts that the genetic conservation within rabbit species is high across the world; however, the available data  for analysis is less to support the statement. The obtained sequence information would be useful for the generation of Type-I interferon  based therapeutics for rabbit and other mammalian species.
Keywords: 3D structure analysis; Bioinformatic analysis; Liver; Interferon-ε; Rabbit